Anti-fogging agent composition, and Anti-fogging article having Anti-fogging coating film

The anti-fog agent composition, featuring a (meth)acrylate copolymer, epoxy compound, and surfactant, addresses the degradation of anti-fog coatings in high temperature and humidity environments by creating a durable, transparent, and effective anti-fog coating film.

JP2025039042APending Publication Date: 2025-03-21NOF CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145782
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing anti-fog coatings face challenges in maintaining transparency and anti-fog performance, especially in high temperature and high humidity environments, where surfactants can leach and degrade the coating's effectiveness.

Method used

A composition comprising a (meth)acrylate copolymer, an epoxy compound, and a surfactant, specifically formulated to form an anti-fog coating film with enhanced high temperature and high humidity resistance, without the need for a primer layer.

Benefits of technology

The solution provides an anti-fog coating film that maintains excellent transparency and anti-fog performance even in harsh environmental conditions, ensuring prolonged functionality and visibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039042000001
    Figure 2025039042000001
  • Figure 2025039042000002
    Figure 2025039042000002
  • Figure 2025039042000003
    Figure 2025039042000003
Patent Text Reader

Abstract

To provide an anti-fogging agent composition that enables the formation of an anti-fogging coating film having superior resistance to high temperature and high humidity.SOLUTION: An anti-fogging agent composition comprises a copolymer (A), an epoxy compound (B), and a surfactant (C), wherein the copolymer (A) is a (meth)acrylate copolymer derived from a monomer mixture comprising a monomer (A-1) represented by general formula (1), a monomer (A-2) represented by general formula (2), a monomer (A-3) represented by general formula (3), and a monomer (A-4) which is (meth)acrylic acid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antifogging agent composition and an antifogging article having an antifogging coating film. [Background technology]

[0002] When the surface of a transparent material such as glass or plastic falls below the dew point, moisture in the air turns into fine droplets that adhere to the surface of the material. The droplets scatter light and cause the material to become cloudy, reducing the transparency of the material and preventing it from performing its intended function.

[0003] As a method for preventing the occurrence of the above-mentioned fogging (anti-fogging), a method is known in which a solution containing a hydrophilic resin, a surfactant, etc. is applied to the surface of a substrate to form an anti-fogging coating film (dried coating film or hardened coating film) (Patent Document 1). In this method, the surfactant contained in the anti-fogging coating film reduces the contact angle of the attached water droplets, forms a uniform water film, and does not cause light scattering, thereby exerting the anti-fogging effect. Furthermore, in this method, the surfactant quickly reduces the contact angle of the water droplets, so the anti-fogging effect can be exerted quickly.

[0004] Furthermore, when applying an anti-fog coating to an inorganic substrate such as glass, it is common to provide a primer layer formed with a silane coupling agent or the like between the substrate and the anti-fog coating as a pretreatment to ensure adhesion to the substrate. In that case, a two-layer structure consisting of a primer and an anti-fog coating is formed, which requires many steps during painting and heat curing, so from the perspective of improving productivity, an anti-fog coating that can ensure adhesion without pretreatment is desired. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-70759 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, the applications of anti-fog coatings have expanded to a wide range, including vanity mirrors, bathroom mirrors, window glass, windshields of automobiles and aircraft, reflectors, protective glasses, glasses, sunglasses, security cameras, car-mounted cameras, and optical sensors. As the applications expand, anti-fog coatings are now used in various environments, and problems associated with this have arisen. In particular, items such as vanity mirrors and bathroom mirrors used in moist places, window glass used outdoors, and security cameras may be exposed to high temperature and high humidity conditions, so that the surfactant in the anti-fog coating film migrates to the coating film surface and becomes easily eluted, causing problems such as whitening of the anti-fog coating film and reduced functionality and visibility of the item due to reduced anti-fog performance. Therefore, it has become necessary to maintain transparency and anti-fog performance under various usage environments, especially under high temperature and high humidity environments (hereinafter referred to as high temperature and high humidity resistance).

[0007] However, there is a concern that the anti-fog coating film disclosed in Patent Document 1 may lack transparency and anti-fog performance in high-temperature and high-humidity environments.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an anti-fogging agent composition capable of forming an anti-fogging coating film having excellent resistance to high temperatures and high humidity. [Means for solving the problem]

[0009] That is, the present invention comprises the following: [1] A copolymer (A), an epoxy compound (B), and a surfactant (C), the copolymer (A) being represented by general formula (1): [ka] (In general formula (1), R 1 is a hydrogen atom or a methyl group, and R 2 and R 3 are independently a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms.) and a monomer (A-1) represented by general formula (2): [ka] (In general formula (2), R 4 is a hydrogen atom or a methyl group, and R 5 is a straight-chain, branched or cyclic alkyl group having 1 to 12 carbon atoms.) and a monomer (A-2) represented by general formula (3): [ka] (In the general formula (3), n is 1 to 20.) and a monomer mixture containing a monomer (A-4) which is (meth)acrylic acid. [2] The anti-fogging agent composition according to [1], wherein, in the monomer mixture, the proportion of the monomer (A-1) is preferably 20 to 60% by weight, the proportion of the monomer (A-2) is preferably 20 to 60% by weight, the proportion of the monomer (A-3) is preferably 3 to 40% by weight, and the proportion of the monomer (A-4) is preferably 1 to 10% by weight. [3] The antifogging agent composition according to [1] or [2], wherein the amount of the surfactant (C) is preferably 1 part by weight or more and 25 parts by weight or less based on 100 parts by weight of the copolymer (A). [4] The antifogging agent composition according to any one of [1] to [3], wherein the epoxy compound (B) is preferably 5 parts by weight or more and 80 parts by weight or less based on 100 parts by weight of the copolymer (A). [5] An anti-fogging article having an anti-fogging coating film formed from the anti-fogging agent composition according to any one of [1] to [4]. Effect of the Invention

[0010] According to the present invention, there is provided an antifogging agent composition capable of forming an antifogging coating film having excellent resistance to high temperatures and high humidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The antifogging agent composition of the present invention contains a copolymer (A), an epoxy compound (B), and a surfactant (C).

[0012] <Copolymer (A)> The copolymer (A) of the present invention is a (meth)acrylate copolymer obtained from a monomer mixture, and the monomer mixture contains at least the following monomers (A-1) to (A-4).

[0013] <Monomer (A-1)> The monomer (A-1) of the present invention is represented by the general formula (1): [ka] (In general formula (1), R 1 is a hydrogen atom or a methyl group, and R 2 and R 3 are independently a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms.

[0014] Examples of the monomer (A-1) include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, Nn-propyl(meth)acrylamide, Ni-propyl(meth)acrylamide, Nn-butyl(meth)acrylamide, Ni-butyl(meth)acrylamide, Nt-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide. From the viewpoint of improving anti-fogging performance, the monomer (A-1) is preferably N,N-dimethyl(meth)acrylamide or N,N-diethyl(meth)acrylamide, and more preferably N,N-dimethyl(meth)acrylamide. The monomer (A-1) may be used alone or in combination of two or more kinds.

[0015] The proportion of the monomer (A-1) in the monomer mixture is preferably 20 to 60% by weight, more preferably 25% by weight or more, and even more preferably 30% by weight or more, in terms of improving the anti-fogging performance of the anti-fogging coating film, and more preferably 55% by weight or less, and even more preferably 50% by weight or less, in terms of improving the water resistance.

[0016] <Monomer (A-2)> The monomer (A-2) of the present invention is represented by the general formula (2): [ka] (In general formula (2), R 4 is a hydrogen atom or a methyl group, and R 5 is a straight-chain, branched or cyclic alkyl group having 1 to 12 carbon atoms.

[0017] Examples of the monomer (A-2) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and isobornyl (meth)acrylate. From the viewpoint of improving antifogging performance, the monomer (A-2) preferably has 1 to 8 carbon atoms. The monomer (A-2) may be used alone or in combination of two or more kinds.

[0018] The proportion of the monomer (A-2) in the monomer mixture is preferably 20 to 60% by weight. From the viewpoint of improving the water resistance of the anti-fog coating film, the proportion of the monomer (A-2) in the monomer mixture is more preferably 25% by weight or more, and even more preferably 30% by weight or more, and from the viewpoint of improving the anti-fog performance, it is more preferably 55% by weight or less, and even more preferably 50% by weight or less.

[0019] <Monomer (A-3)> The monomer (A-3) of the present invention is represented by the general formula (3): [ka] (wherein in general formula (3), n is 1 to 20).

[0020] Examples of commercially available products containing the monomer (A-3) include products under the trade names "β-CEA" (manufactured by Daicel Allnex Co., Ltd.), "SIPOMER β-CEA-J" and "SIPOMER β-CEA-H" (all manufactured by Solvay Nicca Co., Ltd.). From the viewpoint of improving resistance to high temperature and high humidity, n of the monomer (A-3) is preferably 15 or less, more preferably 10 or less. The monomer (A-3) may be used alone or in combination of two or more types having different numbers of n.

[0021] The proportion of the monomer (A-3) in the monomer mixture is preferably 3 to 40% by weight, more preferably 5% by weight or more, and even more preferably 10% by weight or more, in terms of improving the high temperature and high humidity resistance of the anti-fog coating film, and more preferably 35% by weight or less, and even more preferably 30% by weight or less, in terms of improving the adhesion to the substrate and the water resistance.

[0022] The monomer (A-4) of the present invention is (meth)acrylic acid, and preferably acrylic acid.

[0023] The proportion of the monomer (A-4) in the monomer mixture is preferably 1 to 10% by weight. From the viewpoint of improving the high temperature and high humidity resistance of the anti-fog coating film, the proportion of the monomer (A-4) in the monomer mixture is more preferably 1.5% by weight or more, and even more preferably 2.5% by weight or more, and from the viewpoint of improving the adhesion to the substrate and the water resistance, it is more preferably 8.5% by weight or less, and even more preferably 7.5% by weight or less.

[0024] In addition, the monomer mixture may contain, as monomers other than the monomers (A-1) to (A-4), for example, aromatic vinyl monomers such as styrene, vinyl toluene, and α-methylstyrene; vinyl monomers containing quaternary ammonium salts such as (meth)acryloyloxyethyl trimethyl ammonium chloride and (meth)acryloylaminopropyl trimethyl ammonium chloride; [3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]methyl (meth)acrylate, 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]methyl (meth)acrylate, and the like. acrylic monomers containing ultraviolet absorbing groups such as 2,2,6,6-tetramethylpiperidyl methacrylate and 1,2,2,6,6-pentamethylpiperidyl methacrylate; alicyclic acrylic monomers such as dicyclopentenyl (meth)acrylate and dicyclopentenyloxyethyl (meth)acrylate; itaconic acid, crotonic acid, maleic acid, 2-acryloyloxyethyl-succinic acid, 2-acryloyloxyethylhexahydrofuran; Carboxyl group-containing monomers such as taric acid, 2-acryloyloxyethyl-phthalic acid, acryloyloxyethyl monomethyl tetrahydrophthalate, 3-(1-carboxyethoxy)-1-adamantyl methacrylate, and acrylic acid esters of ω-carboxy-polycaprolactone, as well as their ammonium salts, organic amine salts, and alkali metal salts; sulfonic acids such as styrene sulfonic acid, vinyl sulfonic acid, methallyl sulfonic acid, 2-(meth)acrylamido-2-methylpropane sulfonic acid, and 3-sulfopropyl (meth)acrylate. group-containing vinyl monomers, and their ammonium salts, organic amine salts, and alkali metal salts; phosphoric acid group-containing vinyl monomers, such as 2-(meth)acryloyloxyethyl acid phosphate, and their ammonium salts, organic amine salts, and alkali metal salts; bifunctional acrylic monomers, such as 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol (meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and glycerin di(meth)acrylate;Alkoxysilyl group-containing vinyl monomers such as γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, and vinyltrimethoxysilane; epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, vinyl glycidyl ether, and allyl glycidyl ether; amino group-containing vinyl monomers such as dimethylaminopropyl (meth)acrylamide and dimethylaminoethyl (meth)acrylate; hydroxy group-containing acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (meth)acryloylmorpholine, diacetone (meth)acrylamide, and the like can be used.

[0025] The proportions of the individual monomer components in the monomer mixture forming the copolymer (A) of the present invention will be described below.

[0026] <Method for producing copolymer (A)> The copolymer (A) of the present invention is a copolymer obtained by copolymerizing the monomer mixture. The structure of the copolymer (A) may be any of random copolymers, alternating copolymers, block copolymers and graft copolymers, but a random copolymer is preferred from the viewpoint of improving the effects of the antifogging agent composition, including antifogging performance, and easily adjusting the antifogging agent composition. As a polymerization method for obtaining the copolymer (A), various known polymerization methods such as radical polymerization, cationic polymerization, cationic living polymerization and anionic living polymerization are adopted, but the radical polymerization method is preferred from the viewpoint of ease of industrial productivity and wide-ranging performance. As the radical polymerization method, a normal bulk polymerization method, suspension polymerization method, solution polymerization method, emulsion polymerization method and the like are adopted, but the solution polymerization method is preferred from the viewpoint of being able to be used as an antifogging agent composition as it is after polymerization.

[0027] Examples of the polymerization solvent used in the solution polymerization method include alcohol-based solvents such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, and diacetone alcohol; glycol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxy-1-butanol, 3-methoxy-3-methyl-1-butanol, and diethylene glycol ethyl methyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran and dioxane; ester-based solvents such as methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, ethyl lactate, and 2-methoxy-1-methylethyl acetate; aromatic solvents such as benzene, toluene, and xylene; amide-based solvents such as formamide and dimethylformamide; and water. The polymerization solvent may be used alone or in combination of two or more.

[0028] In addition, it is preferable to use a polymerization solvent having a boiling point of less than 180°C at 1 atmosphere, since solvents with extremely high boiling points may impair adhesion to the substrate when the anti-fog coating film is dried and heat-cured due to residual solvent.

[0029] The radical polymerization initiator may be a commonly used organic peroxide, an azo compound, or the like. Examples of the organic peroxide include benzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-hexanoate, t-butylperoxypivalate, and t-hexylperoxypivalate. Examples of the azo compound include 2,2'-azobisisobutyronitrile and 2,2'-azobis-2-methylbutyronitrile. The radical polymerization initiator may be used alone or in combination of two or more.

[0030] The amount of the radical polymerization initiator added is preferably 0.01 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of the monomer mixture. The radical polymerization initiator is preferably added dropwise to a reaction vessel while polymerization is carried out, since this makes it easier to control heat generated by polymerization. The temperature at which the polymerization reaction is carried out is appropriately changed depending on the type of radical polymerization initiator used, but is preferably 30°C or more and 150°C or less, more preferably 40°C or more and 100°C or less, in terms of industrial production.

[0031] The weight average molecular weight (Mw) of the copolymer (A) is preferably 3,000 or more, more preferably 5,000 or more, from the viewpoint of imparting water resistance to the anti-fog coating film, and is preferably 200,000 or less, more preferably 150,000 or less, from the viewpoint of improving the coatability and handleability of the anti-fog agent composition.

[0032] The weight average molecular weight (Mw) of the copolymer (A) can be determined by a GPC method using a sample that is dissolved in tetrahydrofuran to prepare a 0.5 wt% solution and filtered through a 0.45 μm membrane filter, and can be measured under the following conditions. <Measurement of weight average molecular weight (Mw)> Analytical equipment: HLC-8320GPC (Tosoh Corporation) Column: TSKgel SuperMultipore HZ-M (2 columns) (Tosoh Corporation) Column size: 4.6 x 150 mm Eluent: Tetrahydrofuran Flow rate: 0.35mL / min Detector: Differential refractometer Column temperature: 40℃ Standard sample: polystyrene

[0033] <Epoxy compound (B)> The epoxy compound (B) of the present invention is a compound having two or more epoxy groups in one molecule, such as glycidyl ether, and has the function of forming a crosslinked structure in the copolymer by reacting with the copolymer (A) to crosslink between the molecules.

[0034] Examples of the glycidyl ether include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerin diglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, phthalic acid diglycidyl ester, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, an epoxidation reaction product of pentaerythritol tetraallyl ether with hydrogen peroxide, and an epoxidation reaction product of 2,2'-diallyl bisphenol A diallyl ether with hydrogen peroxide.

[0035] Examples of commercially available products of the epoxy compound (B) include trade names such as "Denacol EX-810", "Denacol EX-850", "Denacol EX-861", "Denacol EX-201", "Denacol EX-211", "Denacol EX-212", "Denacol EX-252", "Denacol EX-721", "Denacol EX-920", "Denacol EX-612", "Denacol EX-614", "Denacol EX-614B", "Denacol EX-622", "Denacol EX-313", "Denacol EX-314", "Denacol EX-321", "Denacol EX-321L", "Denacol EX -421", "Denacol EX-512", "Denacol EX-521" (all manufactured by Nagase ChemteX Corporation), "Epolight 40E", "Epolight 100E", "Epolight 200E", "Epolight 400E", "Epolight 70P", "Epolight 200P", "Epolight 400P", "Epolight 1500NP", "Epolight 1600", "Epolight 80MF", "Epolight 100MF", "Epolight 4000" (all manufactured by Kyoeisha Chemical Co., Ltd.), "Showfree CDMDG", "Showfree PETG", "Showfree BATG" (all manufactured by Resonac Co., Ltd.), etc. The epoxy compounds may be used alone or in combination of two or more kinds.

[0036] The epoxy compound (B) is preferably 5 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the copolymer (A). From the viewpoint of improving adhesion to a substrate, the epoxy compound (B) is more preferably 10 parts by weight or more and even more preferably 15 parts by weight or more relative to 100 parts by weight of the copolymer (A), and from the viewpoint of improving anti-fogging performance, the epoxy compound (B) is more preferably 70 parts by weight or less and even more preferably 60 parts by weight or less.

[0037] In addition, the copolymer (A) and the epoxy compound (B) preferably have an Ac equivalent / Ep equivalent ratio (hereinafter, Ac / Ep ratio) between the carboxylic acid equivalent (Ac equivalent) of the copolymer (A) and the epoxy equivalent (Ep equivalent) of the epoxy compound (B) in the range of 0.1 to 3.5, more preferably 0.3 to 2.5.

[0038] The Ep equivalent of the epoxy compound (B) is preferably 100 or more, and is preferably 300 or less, more preferably 200 or less, from the viewpoint of improving adhesion to a substrate. The number of functional groups of the epoxy compound (B) is preferably 3 or more, from the viewpoint of improving water resistance.

[0039] <Surfactant (C)> The surfactant (C) of the present invention is at least one selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants. From the viewpoint of improving the anti-fogging performance, the surfactant is preferably a fluorine-containing surfactant.

[0040] Examples of the anionic surfactant include fatty acid salts such as fatty acid alkali metal salts such as sodium oleate and potassium oleate; higher alcohol sulfates such as sodium lauryl sulfate and ammonium lauryl sulfate; alkylbenzene sulfonates and alkylnaphthalene sulfonates such as sodium dodecylbenzene sulfonate and sodium alkylnaphthalene sulfonate; polyoxyethylene sulfate salts such as naphthalene sulfonate formalin condensates, dialkyl sulfosuccinates, dialkyl phosphate salts, and sodium polyoxyethylene alkylphenyl ether sulfate; fluorine-containing anionic surfactants such as perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, and perfluoroalkyl phosphate esters. From the viewpoint of improving the anti-fogging performance, the anionic surfactant is preferably a dialkyl sulfosuccinate or a fluorine-containing anionic surfactant, and more preferably a fluorine-containing anionic surfactant. The anionic surfactant may be used alone or in combination of two or more.

[0041] Examples of the cationic surfactant include amine salts such as laurylamine acetate, triethanolamine monoformate, and stearamidoethyl diethylamine acetate; alkyl trimethyl ammonium salts such as lauryl trimethyl ammonium chloride and stearyl trimethyl ammonium chloride; dialkyl dimethyl ammonium salts such as dilauryl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, and stearyl dimethyl benzyl ammonium chloride; hydroxyl-containing ammonium salts such as ricinoleamidopropyl ethyl dimonium ethosulfate, ricinoleamidopropyl trimonium chloride, and ricinoleamidopropyl trimonium methosulfate; and fluorine-containing cationic surfactants. From the viewpoint of improving the anti-fogging performance, the cationic surfactant is preferably an alkyl trimethyl ammonium salt, a dialkyl dimethyl ammonium salt, a hydroxyl-containing ammonium salt, or a fluorine-containing cationic surfactant, and more preferably a fluorine-containing cationic surfactant. From the viewpoint of improving the anti-fogging durability, the cationic surfactant is preferably a hydroxyl-containing ammonium salt. The cationic surfactant may be used alone or in combination of two or more kinds.

[0042] Examples of the nonionic surfactants include polyoxyethylene higher alcohol ethers such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenol and polyoxyethylene nonylphenol; polyoxyethylene sorbitan fatty acid esters such as polypropylene glycol ethylene oxide adduct, polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; phosphates such as alkyl phosphates and polyoxyethylene alkyl ether phosphates; and perfluoroalkylamines. Fluorine-containing nonionic surfactants such as oxide, perfluoroalkenylamine oxide, perfluoroalkylethylene oxide adduct, perfluoroalkenylethylene oxide adduct, oligomer having perfluoroalkyl group and hydrophilic group, oligomer having perfluoroalkenyl group and hydrophilic group, oligomer having perfluoroalkyl group and lipophilic group, oligomer having perfluoroalkenyl group and lipophilic group, oligomer having perfluoroalkyl group, hydrophilic group and lipophilic group, oligomer having perfluoroalkenyl group, hydrophilic group and lipophilic group, oligomer having perfluoroalkenyl group, hydrophilic group and lipophilic group, and oligomer having perfluoroalkenyl group, hydrophilic group and lipophilic group; sugar esters, cellulose ethers, etc. are listed. The nonionic surfactant is preferably a fluorine-containing nonionic surfactant from the viewpoint of improving anti-fogging performance. The nonionic surfactant may be used alone or in combination of two or more kinds.

[0043] Examples of the amphoteric surfactant include fatty acid amphoteric surfactants such as dimethyl alkyl lauryl betaine, dimethyl alkyl stearyl betaine, lauryl dimethyl amino acetic acid betaine, and lauric acid amidopropyl dimethyl amino acetic acid betaine; sulfonic acid amphoteric surfactants such as dimethyl alkyl sulfobetaine; alkyl glycine, and fluorine-containing betaine surfactants. From the viewpoint of improving anti-fogging performance, the amphoteric surfactant is preferably a fluorine-containing betaine surfactant. The amphoteric surfactant may be used alone or in combination of two or more kinds.

[0044] From the viewpoint of obtaining good anti-fogging performance with a relatively small amount, the surfactant (C) is preferably an anionic surfactant alone, a combination of an anionic surfactant and a cationic surfactant, a combination of an anionic surfactant and a nonionic surfactant, or a combination of an anionic surfactant and an amphoteric surfactant, and more preferably a combination of an anionic surfactant, a nonionic surfactant, and a betaine surfactant. In any combination, when all the surfactants contain fluorine, the surface tension of the anti-fogging coating film against water can be reduced more effectively, and therefore higher anti-fogging performance can be obtained.

[0045] The surfactant (C) is preferably 1 part by weight or more and 25 parts by weight or less relative to 100 parts by weight of the copolymer (A). From the viewpoint of improving anti-fogging performance, the surfactant (C) is more preferably 2 parts by weight or more and even more preferably 3 parts by weight or more relative to 100 parts by weight of the copolymer (A), and from the viewpoint of improving transparency, the surfactant (C) is more preferably 20 parts by weight or less and even more preferably 15 parts by weight or less.

[0046] The antifogging agent composition of the present invention may contain a dilution solvent from the viewpoint of improving coating workability.

[0047] The dilution solvent is used for the purpose of adjusting the solid content and viscosity suitable for coating the antifogging agent composition. Examples of the dilution solvent include the same as the polymerization solvent for the copolymer (A). The dilution solvent may be used alone or in combination of two or more. The solid content and viscosity suitable for coating vary depending on the coating method, but in the case of the spray coating method, the total weight percent of the copolymer (A) and the epoxy compound (B) in the antifogging agent composition is preferably 3 weight percent or more, more preferably 5 weight percent or more, and more preferably 30 weight percent or less, and more preferably 20 weight percent or less.

[0048] In order to improve adhesion to a substrate, a silane coupling agent which reacts with the crosslinking points of the anti-fog coating film may be added to the anti-fog composition of the present invention.

[0049] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyldimethoxysilane, 3-glycidoxypropyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethoxysilane, 8-glycidoxyoctyltrimethoxysilane, and epoxy group-containing oligomer-type coupling agents; N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-ethoxysilyl-N -(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, amino group-containing oligomer type coupling agents and other amino group-containing silane coupling agents; mercapto group-containing silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, mercapto group-containing oligomer type silane coupling agents; and 3-trimethoxysilylpropylsuccinic anhydride.

[0050] Examples of commercially available silane coupling agents include trade names such as "KBM-402", "KBE-402", "KBM-403", "KBE-403", "KBE-303", "KBE-4803", "X-12-981S", "X-12-984S", "KR-516", "KR-517", "KBM-602", "KBM-603", "KBM-903", "KBE-903", and "KBE -9103P", "X-12-1172ES", "KBM-573", "KBM-575", "KBM-6803", "X-12-972F", "X-12-967C", "KBM-802", "KBM-803", "X-12-1154", "X-12-1156", "KR-518", "KR-519", "X-12-1056ES" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "DOWSIL Z-6040 Silane", "DOWSIL Z-6043 Silane", "DOWSIL Z-6011 Silane", "DOWSIL Z-6094 Silane", "DOWSIL Z-6062 Silane" (all manufactured by Dow Toray Co., Ltd.), etc. The silane coupling agent may be used alone or in combination of two or more kinds.

[0051] When the silane coupling agent is used, the amount of the silane coupling agent is preferably 0.01 parts by weight or more and 10 parts by weight or less, more preferably 0.05 parts by weight or more and 5 parts by weight or less, and even more preferably 0.1 parts by weight or more and 3 parts by weight or less, relative to 100 parts by weight of the copolymer (A).

[0052] The antifogging agent composition of the present invention may contain a curing catalyst from the viewpoint of enabling heat curing at a low temperature in a short time.

[0053] Examples of the curing catalyst include Lewis acids such as tin tetrachloride, zinc trichloride, titanium tetrachloride, tetraisopropyl orthotitanate, aluminum trichloride, boron trichloride, boron tribromide, tetrahydrofuran borane, and boron trifluoride diethyl ether complex; tertiary alkylamines such as triethylamine, triethylenediamine, 2-dimethylaminoethanol, pentamethyldiethylenetriamine, and bis(2-(dimethylamino)ethyl)ether; imidazole, 8-diazabicyclo[5.4.0]-7-undecene, 4-aminopyridine, and 4-dimethylaminopyridine. tertiary aromatic amines; ammonium salts such as tridecanylmethylammonium salt, dilauryldimethylammonium salt, trioctylmethylammonium salt; organic titanium compounds such as tetraisopropyl titanate, tetraoctyl titanate, titanium acetylacetonate, and titanium phosphate complex; organic zirconium compounds such as zirconium tetraacetylacetonate triphenyl, zirconium tetraacetylacetonate, and zirconium monoacetylacetonate; phosphines, tetraphenylphosphonium tetraphenylborate, etc. The curing catalyst may be used alone or in combination of two or more.

[0054] When the curing catalyst is used, the amount of the curing catalyst is preferably 0.01 parts by weight or more and 10 parts by weight or less, more preferably 0.05 parts by weight or more and 5 parts by weight or less, and even more preferably 0.1 parts by weight or more and 3 parts by weight or less, relative to 100 parts by weight of the copolymer (A).

[0055] A leveling agent may be added to the antifogging agent composition of the present invention from the viewpoint of making the surface of the antifogging coating film smoother.

[0056] Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyether-modified polydimethylpolysiloxane, organic modified polysiloxane, polyether macromer modified acrylate, acrylic polymer, acrylic silicone polymer, fluorine-containing acrylic polymer, and amphiphilic oligomer.

[0057] Examples of commercially available leveling agents include those under the trade names "BYK-300", "BYK-320", "BYK-306", "BYK-307", "BYK-310", "BYK-313", "BYK-315N", "BYK-320", "BYK-322", "BYK-323", "BYK-325", "BYK-330", "BYK-331", "BYK-333", "BYK-342", "BYK-345 / 346", "BYK-347", "BYK-348", "BYK-349", "BYK-370", "BYK-377", "BYK-378", "BYK-3455", and "BYK-3560" (all manufactured by BYK-Chemie Co., Ltd.); and those under the trade names "KP-323", "KP-341", "KP-104", "KP-110", "KP-112", and "KF-35 1A", "KF-352A", "KF-353", "KF-354L", "KF-355A", "KF-651A", "KF-945", "KF-640", "KF-642" (all manufactured by Shin-Etsu Silicones Co., Ltd.), trade names: "Disparlon 1970", "Disparlon 230", "Disparlon 1711EF", "Disparlon 1761", "Disparlon LS-001", "Disparlon LS-050", "Disparlon LS-460", "Disparlon LS-480" (all manufactured by Kusumoto Chemicals Co., Ltd.), "Polyflow KL-100", "Polyflow KL-700", "Polyflow KL-850", "Polyflow KL-900", "LE-302N", "LE-304", "LE-604", "LE-605" (all manufactured by Kyoeisha Chemical Co., Ltd.), and the like. The leveling agents may be used alone or in combination of two or more.

[0058] When the leveling agent is used, the amount of the leveling agent is preferably 0.01 parts by weight or more and 10 parts by weight or less, more preferably 0.05 parts by weight or more and 5 parts by weight or less, and even more preferably 0.1 parts by weight or more and 3 parts by weight or less, relative to 100 parts by weight of the copolymer (A).

[0059] In addition to the above-mentioned components, the antifogging agent composition of the present invention may contain various conventional additives such as antioxidants, ultraviolet absorbers, light stabilizers, etc. The amount of the other components added may be the conventional amount for each additive, and is usually 20 parts by weight or less per 100 parts by weight of the copolymer (A).

[0060] <Anti-fog articles> The anti-fogging article of the present invention is one in which the anti-fogging agent composition is applied to a substrate (subject to be coated) by a coating method used for ordinary paints, and then heat-cured to form an anti-fogging coating film on the surface of the substrate (subject to be coated). Note that a drying step can be provided before the heat-curing step in order to volatilize and dry the solvent contained in the anti-fogging coating film immediately after application.

[0061] The substrate (object to be coated) may be of any type and is not particularly limited, and examples thereof include resin substrates such as polymethyl methacrylate resin, polycarbonate resin, polystyrene resin, acrylonitrile-styrene copolymer resin, polyvinyl chloride resin, acetate resin, ABS resin, polyester resin, polyamide resin, etc.; and inorganic substrates such as soda-lime glass, borosilicate glass, alkali-free glass, anti-reflective glass, fused quartz glass, synthetic quartz glass, etc. The shape of the substrate is not limited, and examples thereof include films, sheets, and three-dimensional molded products.

[0062] When coating the substrate (subject to be coated), it is preferable to remove any foreign matter adhering to the surface of the substrate (subject to be coated) before coating in order to increase the wettability of the antifogging agent composition to the substrate (subject to be coated) and prevent repellency. Examples of the method include dust removal using high-pressure air or ionized air, ultrasonic cleaning using an aqueous detergent solution or alcohol solvent or an alkaline solution, wiping using an alcohol solvent, polishing with cerium oxide, and cleaning with ultraviolet light and ozone. Examples of the coating method include immersion, flow coating, roll coating, bar coating, spray coating, and spin coating.

[0063] The drying is usually carried out under conditions of a temperature of 20 to 50° C. for 0.5 to 10 minutes.

[0064] When the substrate is a resin material, the heating temperature is preferably set to a temperature equal to or lower than the thermal deformation temperature of the resin material, and when the substrate is an inorganic substrate (such as glass), the heating temperature is preferably set to a temperature equal to or lower than the decomposition temperature of additives such as surfactant (C). The heating time is affected by the heating temperature and should be set appropriately. For example, when the heating temperature is 150°C, the heating time is preferably 30 minutes or more, more preferably 60 minutes or more.

[0065] The thickness of the anti-fog coating film is preferably from 0.5 μm to 20 μm, more preferably from 1 μm to 10 μm, from the viewpoint of obtaining good anti-fog performance and good coating film appearance.

[0066] The antifogging article is more suitable for use in an environment where condensation is likely to occur, and is not limited in its application. Examples of the antifogging article include vehicle lighting (headlights, auxiliary headlights, width lights, license plate lights, tail lights, parking lights, back-up lights, turn signals, auxiliary turn signals, emergency flashers, etc.) for automobiles, vanity mirrors, bathroom mirrors, general window glass, automobile and aircraft windshields, reflectors, protective glasses, glasses, sunglasses, security cameras, car-mounted cameras, optical sensors, etc. EXAMPLES

[0067] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0068] Prior to the production of copolymer (A), "β-CEA" manufactured by Daicel Allnex Co., Ltd. was used as the monomer (A-3) and monomer (A-4) to be used in the production. β-CEA is a mixture containing 80% of monomer (A-3) in which n is 1 to 5 in the general formula (3) and 20% of monomer (A-4) acrylic acid (hereinafter, monomer (A-3) contained in β-CEA may be collectively referred to as "CEA" and monomer (A-4) may be collectively referred to as "AAc").

[0069] <Example 1> <Production of Copolymer (A)> In a reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 269 parts by weight of diacetone alcohol was charged as a polymerization solvent, and heated to 70°C while blowing in nitrogen gas. Next, a solution of 35 parts by weight of N,N-dimethylacrylamide as monomer (A-1), 40 parts by weight of cyclohexyl acrylate as monomer (A-2), 25 parts by weight of monomer (A-3) and monomer (A-4) (trade name: "β-CEA", manufactured by Daicel Allnex Co., Ltd.) and 15 parts by weight of diacetone alcohol mixed, and a solution of 1.1 parts by weight of t-hexylperoxyneodecanoate (trade name: "Perhexyl ND", manufactured by NOF Corp., active ingredient 70% by weight) dissolved in 10 parts by weight of diacetone alcohol as a radical polymerization initiator were dropped over 3 hours. After the dropwise addition, the mixture was stirred for 30 minutes, and then a solution of 0.6 parts by weight of Perhexyl ND dissolved in 4.0 parts by weight of diacetone alcohol was dropped over 1 hour. After the dropwise addition, the mixture was stirred for 2 hours, and then cooled to produce a solution of copolymer (A). The weight average molecular weight of copolymer (A) was measured by gel permeation chromatography and found to be 80,000. The solid content of this solution of copolymer (A) was 25.0%. At this time, the Ac equivalent of copolymer (A) was calculated to be 56.1×1000 / (365×25 / 100)=614, since 25 parts by weight of β-CEA (monomer (A-3) and monomer (A-4)) was contained in 100 parts by weight of copolymer (A) and the acid value of β-CEA was 365 mg / KOHg.

[0070] <Production of antifogging agent composition> For 400 parts by weight (solid content 25%) of the copolymer (A) obtained above, 25 parts by weight of glycerol polyglycidyl ether (trade name: "Denacol EX-313", manufactured by Nagase ChemteX Corporation, Ep equivalent: 141) was used as the epoxy compound (B), and the composition of the surfactant (C) shown in Table 1 (3.0 parts by weight of a fluorine-containing anionic surfactant (trade name: "Ftergent 100", manufactured by Neos Corporation), 0.2 parts by weight of a fluorine-containing nonionic surfactant (trade name: "Ftergent 222F", manufactured by Neos Corporation), and fluorine-containing betaine (trade name: "Ftergent 222F", manufactured by Neos Corporation)) was used as the surfactant (C). A system surfactant (trade name: "Ftergent 400SW", manufactured by Neos Co., Ltd.) was mixed in an amount of 0.5 parts by weight, a curing catalyst was used as the zirconium tetraacetylacetonate (trade name: "Orgatics ZC-700", manufactured by Matsumoto Fine Chemical Co., Ltd., active ingredient 20% by weight), 0.5 parts by weight, a leveling agent was used as the polyether-modified polydimethylsiloxane (trade name: "BYK-333", manufactured by BYK Japan Co., Ltd.), and 960 parts by weight of propylene glycol monomethyl ether was used as the dilution solvent to produce an antifogging agent composition. At this time, the Ac / Ep ratio was calculated as follows. {Parts by weight of (A) (in terms of active ingredient) / Ac equivalent of (A)} / {Parts by weight of (B) (in terms of active ingredient) / Ep equivalent of (B)}={100 / 614} / {25 / 141}=0.92.

[0071] <Example of surfactant (C) blend> [Table 1]

[0072] <Preparation of anti-fogging article> In an environment set at 25°C and a relative humidity of 30%, the anti-fog composition obtained above was spray-coated onto soda-lime glass so that the anti-fog coating film after curing had a thickness of about 2 to 3 μm, and then heat-cured at 150°C for 60 minutes to produce an anti-fog article (test piece) having an anti-fog coating film.

[0073] The test pieces obtained above were used to carry out the evaluation methods (1) to (5) below, and the results are shown in Table 2.

[0074] <(1) Evaluation of transparency> In accordance with the test method for total light transmittance of plastic materials (JIS-K7361-1), a haze meter (HAZE METER HDN5000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the haze value of the test piece (light source: white LED, luminous flux: 14 mm, temperature: 25°C, humidity: 50%) and evaluate it on the following four-level scale. A rating of B- or above, which is acceptable for practical use, was considered to be a pass. The haze value of soda-lime glass with a thickness of 2 mm was 0.25. A: Haze value is 0.25 or more and less than 0.40 B+: Haze value is 0.40 or more and less than 0.50 B-: Haze value is 0.50 or more and less than 0.60 C: Haze value is 0.60 or more

[0075] <(2) Evaluation of adhesion> The anti-fog film of the test piece was cut into an area of ​​1 cm length and 1 cm width at 1 mm intervals in both directions using a cutter knife to create 100 grids. Cellophane tape was pressed onto the surface of the grid, and when it was quickly peeled off, the appearance was visually observed and rated on the following four-point scale. A rating of B- or higher, which is acceptable for practical use, was deemed a pass. A: No peeling was observed at all. B+: Slight peeling is observed at the intersection of the cuts. B-: Peeling is observed in 1 to 10 squares. C: Peeling was observed in 10 or more squares.

[0076] <(3) Evaluation of anti-fogging performance> The test piece was placed 2 cm above the water surface in a hot water bath kept at 80°C, with the anti-fog coating surface facing down, and the anti-fog coating was continuously irradiated with steam from the hot water bath. The presence or absence of fogging 10 seconds after irradiation was visually evaluated on the following four-point scale. A rating of B- or above, which is acceptable for practical use, was considered a pass. A: A water film is formed immediately after steam irradiation and the glass does not become cloudy. B+: A momentary clouding is observed immediately after steam irradiation, but a water film is quickly formed and the clouding does not occur. B-: Clouding is observed immediately after steam irradiation, but a water film is formed and the clouding does not occur. C: Clouding was observed immediately after steam irradiation, and no water film was formed.

[0077] <(4) Evaluation of transparency and resistance to high temperature and humidity> The test piece was left to stand at 80°C and 85% RH for 48 hours, and then left to stand at room temperature for 1 hour. The transparency of the anti-fog coating film was evaluated using the test method in (1) and rated on the following four-point scale. A rating of B- or higher, which is acceptable for practical use, was considered a pass. A: Haze value is 0.25 or more and less than 0.40 B+: Haze value is 0.40 or more and less than 0.50 B-: Haze value is 0.50 or more and less than 0.60 C: Haze value is 0.60 or more

[0078] <(5) Evaluation of anti-fogging performance against high temperature and humidity> The test pieces were left to stand at 80°C and 85% RH for 48 hours, and then at room temperature for 1 hour. The anti-fogging performance of the anti-fogging coating was evaluated using the test method described in (3) and rated on the following four-point scale. A rating of B- or higher, which is acceptable for practical use, was deemed to be a pass. A: A water film is formed immediately after steam irradiation and the glass does not become cloudy. B+: A momentary clouding is observed immediately after steam irradiation, but a water film is quickly formed and the clouding does not occur. B-: Clouding is observed immediately after steam irradiation, but a water film is formed and the clouding does not occur. C: Clouding was observed immediately after steam irradiation, and no water film was formed.

[0079] <Examples 2 to 15 and Comparative Examples 1 to 2> <Production of antifogging agent composition and preparation of antifogging article> Antifogging agent compositions of Examples 2 to 15 and Comparative Examples 1 and 2 were produced in the same manner as in Example 1, except that the raw materials of Example 1 were changed to the composition of surfactant (C) shown in Table 1, and the raw materials and their blending amounts shown in Tables 2 to 4. Furthermore, antifogging articles (test pieces) having antifogging coating films of Examples 2 to 15 and Comparative Examples 1 and 2 were produced in the same manner as in Example 1.

[0080] The results obtained by using the test pieces obtained above and the evaluation methods (1) to (5) above are shown in Tables 2 to 4.

[0081] [Table 2]

[0082] [Table 3]

[0083] [Table 4]

[0084] In Tables 2 to 4, monomers (A-1) to (A-4) are: DMAA is N,N-dimethylacrylamide; DEAA, N,N-diethylacrylamide; CHA is cyclohexyl acrylate; BA, butyl acrylate; LA, lauryl acrylate; CEA is a monomer represented by the above general formula (3) in which n is 1 to 5; AAc represents acrylic acid.

[0085] In Table 4, other monomers include: HOAMS refers to 2-acryloyloxyethyl succinic acid (product name: "HOA-MS(N)", manufactured by Kyoeisha Chemical Co., Ltd.).

[0086] In Tables 2 to 4, the epoxy compound (B) is EX810 is ethylene glycol diglycidyl ether (product name: "Denacol EX-810", manufactured by Nagase ChemteX Corporation, Ep equivalent: 113, number of functional groups: 2); EX313 is glycerol polyglycidyl ether (trade name: "Denacol EX-313", Nagase ChemteX Corporation, Ep equivalent: 141, number of functional groups: including 2 and 3); EX614B indicates sorbitol polyglycidyl ether (product name: "Denacol EX-614B", manufactured by Nagase ChemteX Corporation, Ep equivalent: 173, number of functional groups: 4);

[0087] In Table 1, surfactant (C) is F100 is a fluorine-containing anionic surfactant (product name: "Ftergent 100", manufactured by Neos Co., Ltd.); F222F is a fluorine-containing nonionic surfactant (product name: "Ftergent 222F", manufactured by Neos Co., Ltd.); F400SW indicates a fluorine-containing betaine surfactant (product name: "Ftergent 400SW", manufactured by Neos Co., Ltd.);

[0088] In Tables 2 to 4, as the silane coupling agent, KBM403 indicates 3-glycidoxypropyltrimethoxysilane (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd., Ep equivalent: 236.3).

[0089] In Tables 2 to 4, the curing catalyst is ZC700 indicates zirconium tetraacetylacetonate (trade name "Orgatix ZC-700", manufactured by Matsumoto Fine Chemical Co., Ltd., active ingredient 20% by weight).

[0090] In Tables 2 to 4, as the leveling agent, BYK333 refers to polyether-modified polydimethylsiloxane (product name: "BYK-333", manufactured by BYK Japan K.K.).

[0091] As shown in Tables 2 to 4, the antifogging agent compositions of Examples 1 to 15 can form antifogging coating films that maintain transparency, adhesion, antifogging performance, and resistance to high temperatures and high humidity.

[0092] On the other hand, as shown in Table 4, in Comparative Example 1, since the copolymer (A) did not contain the monomer (A-3), the resistance to high temperature and high humidity was reduced. In Comparative Example 2, in the composition of Example 2, HOAMS was introduced as another carboxyl group-containing monomer instead of the monomer (A-3) and the monomer (A-4) in the copolymer (A), and the resistance to high temperature and high humidity was reduced.

Claims

1. The composition comprises a copolymer (A), an epoxy compound (B), and a surfactant (C), The copolymer (A) is represented by the general formula (1): 【Chemistry 1】 (In general formula (1), R 1 is a hydrogen atom or a methyl group, R 2 and R 3 are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; General formula (2): 【Chemistry 2】 (In general formula (2), R 4 is a hydrogen atom or a methyl group, R 5 is a straight-chain, branched or cyclic alkyl group having 1 to 12 carbon atoms; General formula (3): 【Chemistry 3】 (wherein n is 1 to 20) An antifogging agent composition, which is a (meth)acrylate copolymer obtained from a monomer mixture containing a monomer (A-4) which is (meth)acrylic acid.

2. 2. The antifogging agent composition according to claim 1, wherein, in the monomer mixture, the proportion of the monomer (A-1) is 20 to 60% by weight, the proportion of the monomer (A-2) is 20 to 60% by weight, the proportion of the monomer (A-3) is 3 to 40% by weight, and the proportion of the monomer (A-4) is 1 to 10% by weight.

3. 3. The antifogging agent composition according to claim 1, wherein the surfactant (C) is contained in an amount of 1 part by weight or more and 25 parts by weight or less based on 100 parts by weight of the copolymer (A).

4. 3. The antifogging agent composition according to claim 1, wherein the epoxy compound (B) is contained in an amount of 5 parts by weight or more and 80 parts by weight or less based on 100 parts by weight of the copolymer (A).

5. 3. An anti-fogging article having an anti-fogging coating film formed from the anti-fogging agent composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Anti-fogging coating agent

    JP2021070759A